1990
DOI: 10.2190/gbpm-h9cj-ln22-02tt
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Control and Acceptance of the Decision to Enter a Nursing Home as Predictors of Adjustment

Abstract: A longitudinal study of newly admitted nursing home residents examined the effects of perceived control over the relocation decision and acceptance of the relocation in general as determinants of changes in functional health and morale. Perceived control had positive effects on health during the first month of residency but negative effects on health and morale between the second and fourth months. On the other hand, acceptance had positive effects on both health and morale between the second and fourth months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…However, only up to 20% of the variance in the behaviour problems could be explained by the variables that were studied. Therefore, the variance in behaviour was due to other variables such as neurological changes in the brain, nursing staffs variable approach to patients (which may provoke or reduce behaviour), behavioural disturbance in other residents, the physical environment of the nursing home, differences in the quality of the relationships before and after admission, and the number and type of lifetime losses since relocation to a nursing home could be seen as a loss of autonomy and independence (Davidson and O'Connor, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, only up to 20% of the variance in the behaviour problems could be explained by the variables that were studied. Therefore, the variance in behaviour was due to other variables such as neurological changes in the brain, nursing staffs variable approach to patients (which may provoke or reduce behaviour), behavioural disturbance in other residents, the physical environment of the nursing home, differences in the quality of the relationships before and after admission, and the number and type of lifetime losses since relocation to a nursing home could be seen as a loss of autonomy and independence (Davidson and O'Connor, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies suggest that exerting control over future care arrangements promotes subjective well-being and enhances satisfaction with the receipt of care (Harel & Noelker, 1982;Lieberman & Tobin, 1983;Reinardy, 1992;Reinardy & Kane, 1999), as long as one's expectations become a reality (Davidson & O'Connor, 1990). However, because there are individual differences in the need for taking control (Ziegler & Reid, 1979), those who do not wish to take control over the source of future care would probably benefit less from planning in advance for future health care needs.…”
Section: Positive Effects Of Preparation For Future Care Needsmentioning
confidence: 99%
“…Young (1998) found that residents who initiate their moves to retirement housing have the highest levels of satisfaction with both the decision and the overall moving process and so felt more at home in their new surroundings. Numerous studies of nursing home relocation have also demonstrated a positive relationship between control of decision making and resident well-being (Davidson & O’Connor, 1990; Forbes & Hoffart, 1998; Holzapfel et al, 1992; Mikhail, 1992). …”
mentioning
confidence: 99%